Implikasi Hukum Dalam Transfer Jaminan Fidusia Tanpa Persetujuan Penerima Fidusia (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
The aim of this research is to identify and analyze the factors that drive fiduciaries to transfer fiduciary objects to third parties without the consent of the fiduciary receiver. Furthermore, this study also aims to analyze the legal protection provided to the fiduciary receiver concerning the transfer of fiduciary collateral conducted by the fiduciary without the consent of the fiduciary receiver. Lastly, this research will examine the criminal liability that arises from the transfer of fiduciary collateral without the consent of the fiduciary receiver.In conducting this research, the researcher employs a normative-empirical legal research approach, utilizing the statutory approach, comparative approach, and case approach. Criminal liability in the transfer of fiduciary collateral without the consent of the receiver may result in criminal responsibility for the fiduciary. Article 36 of Law Number 42 of 1999 concerning Fiduciary Collateral stipulates that a fiduciary who transfers the collateral object without written consent from the fiduciary receiver may be held criminally accountable..